Forensic entomology an introduction - Gennard, Dorothy E. (John Wiley & Sons, 2012)
Forensic Entomology provides undergraduates with a concise introduction to the subject. The book is written with the clarity necessary for students starting out in entomology yet authoritative enough to prove useful for more experienced researchers.